Pregnancy Diagnosis: An Essential Factor in Evaluating Farm Breeding Efficiency - V Haripriya, Ankita Agarwal, Sachin Sharma (Revista Electronica de Veterinaria, 2024)
The purpose of the research is to assess the organized farm’s conception rate (CR) and pregnancy diagnosis-positive rate (PD-PR) to make appropriate management decisions. An analysis was conducted on a one-year record of PD and Artificial Insemination (A.I.) of dairy animals (N=1325, consisting of 298 buffaloes and 1027 cows). Buffaloes and cows were diagnosed with per rectal pregnancy after an average of 73.85 and 74.89 after A.I. The total PD-PR value of cattle is greater than that of buffaloes (71.92% and 62.95%, respectively). Buffaloes have a greater overall CR tendency in comparison to cattle, with rates of 42.65% and 50.29%, respectively. The PD-PR values in buffaloes and cattle were 14.31% and 25.60% lower, respectively, when compared to the farm standard of 85%. During the winter season, cattle and buffaloes exhibited greater PD-PR and CR values, with cattle showing values of 61.50% and 38.08%, respectively and buffaloes showing values of 59.55% and 60.91%, respectively. However, cattle exhibited lower values of PD-PR (70.34%) and CR (23.44%) during rainy seasons, while buffaloes showed lower values of PD-PR (60.25%) and CR (61.84%) during summer seasons. High humidity and heat stress had an essential impact on the development of CR and oestrus symptoms.